2MASS J15460752−6258042: a mid-M dwarf hosting a prolonged accretion disc. Issue 1 (13th March 2020) - Lee, Jinhee; Song, Inseok; Murphy, Simon
ABSTRACT: We report the discovery of the oldest (∼55 Myr) mid-M type star known to host ongoing accretion. 2MASS J15460752–6258042 (2M1546, spectral type M5, 59.2 pc) shows spectroscopic signs of accretion such as strong H α, He i, and [O i ] emission lines, from which we estimate an accretion rate of ∼10 −10 M⊙ yr −1 . Considering the clearly detected infrared excess in all WISE bands, the shape of its spectral energy distribution (SED) and its age, we believe that the star is surrounded by a transitional disc, clearly with some gas still present at inner radii. The position and kinematics of the star from Gaia DR2 and our own radial-velocity measurements suggest membership in the nearby ∼55 Myr-old Argus moving group. At only 59 pc from Earth, 2M1546 is one of the nearest accreting mid-M dwarfs, making it an ideal target for studying the upper limit on the lifetimes of gas-rich discs around low-mass stars.